Cupping Therapy as a Complementary Approach to Enhancing Kidney Health: A Review of Current Evidence - Imran, Tesleem Omotayo (Journal of Public Health Sciences, 2024)
Maintaining good kidney health is of paramount importance for the overall well-being and longevity of an individual., The exploration of complementary and alternative therapeutic practices to support overall health including renal function is a subject of growing interest over the years. Cupping therapy is an example of such intervention which has gained attention for its potential benefits in various health issues, including pain management, recovery, gastrointestinal issues, and preventive therapy. This study summarizes the findings from various studies on the impact of cupping therapy on parameters related to kidney health. The review emphasizes the need for further research to establish the efficacy and safety of cupping therapy as a complementary approach in the maintenance of kidney health, prevention and management of renal disorders, as well as the need for standardized practice of its applications.